The role of tacit knowledge in building core capabilities - an analytical study of the opinions of a sample of employees of the General Company for Mechanical Industries in Alexandria: an analytical study of the opinions of a sample of employees of the General Company for Mechanical Industries in Alexandria - Yasmen kassem‏ Al-Khafaji (Iraqi Journal for Administrative Sciences, 2024)
To distinguish any organization from other competitors is through a unique set of skills, these skills are called core competencies. With today's competition, knowledge is power, in front of other competing organizations. Intellectual capital management can be to be constrained, both large and small organizations have acquired information, and knowledge from organizations can be attributed to improvements This research aim to identify the relationship between tacit knowledge and competencies in The General Company for Mechanical Industries in Alexandria. And for the reason of limited studies that dealt with the relationship between the two variables, especially in the Iraqi environment, the current research sought to address the two variables in order to study and determine the nature of the relationship between them, as well as the theoretical coverage of each. In order to achieve the objective of this research, two main hypotheses were tested; a random sample consisting of 72 employees of the surveyed company. The data were statistically processed using several statistical methods (simple correlation coefficient, simple regression analysis, T test, F test, interpretation coefficient). The research reached several conclusions, most notably as follow: The results of the statistical analysis confirm the acceptance of the first main research hypothesis (the existence of a positive relationship between the tacit knowledge and the competencies. This means that the respondents are aware of the importance of tacit knowledge which contributes to making the intrinsic capabilities more positive to achieve the organizational goals and improve the overall performance, in the sense that improving and increasing efficiency requires a lot of joint work. The company needs other core capabilities, such as the technology capabilities that are the basis of the company and complementary to other capabilities possessed by employees. The research concluded with a number of recommendations, the most important of which is; “The need for management attention in the company in question, for the knowledge of the implicit knowledge to realize the intrinsic capabilities by increasing sales, building a brand, maintaining the competitive and financial position and the company".